Konsep Relativitas dalam Kaitannya dengan Ruang dan Waktu Menurut Albert Einstein - Rivaldo Benediktus Talemba (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The concept of space and time is a complex theory, which is studied from various perspectives. Albert Einstein, a physicist who studied the concept of space and time in the perspective of physics, through his theory of relativity. The theory of relativity describes a unity in space and time. Einstein's relativity rejects some previous views on the absoluteness and absoluteness of things. Einstein used gravity to generalize the theory of uniform linear motion to arbitrary motion. In special relativity, forces are dealt with by ignoring the philosophical problem that forces produce acceleration, which does not allow velocity to remain constant. One can argue that only objects and not observers are accelerated. However, with relativity, objects are equally good observers. We can say that in the view of special relativity, all forces are equal. However, in the view of gravitational relativity, irregular motion is also said to be motion, but only gravity is